(3JGQjN GdTMQ Ydi MhGOK GdSfjfs - (3GdWjH eMeO Hf YeQ HGabjg GdTMQj,J (B1011 (3g` s ((3YHO Gddg Hf UGdM Hf YhO HGYWH s)
(3ChdgG (B:s
(3GdSfI (B((3GdaGJMI (B) (3JSYeGFI ef gLQI GdQShd Udi Gddg Ydjg hSde hgj Chd GdbQf ajgG , hbjd ai GdSfI GdJi bHdgG JhUd GdSdWGf LYaQ Hf YHO Gddg Hf Ydi Hf YeQ GdcKjQi hcGf hUhdg s
(3BNQgG (B:s
(3BNQg ai JQLeI Gdabjg YHO GdQMef Hf Ydi HGZhK HGMQei GdMVQei ai hajGJ SfI Cda (B: " (3hbGd Gdabjg YHO Gddg HGSfLdg ai eOMg hjPcQ cJGHg (B: (3hUdi Gddg eG MfJ QcGH Ydi GdeNJGQ hGdBd GdcQGeG EfJgJ hUdi Gddg Ydi SjOfG eMeO s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3YdjgG Jedc HGSe eMeO Hf SGde Hf Ydhi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs